Comparación de creencias epistemológicas sobre la matemática su enseñanza y aprendizaje de estudiantes en formación de la licenciatura en matemáticas de la UAN. un estudio de caso (2018)
In this degree work we sought to identify the beliefs of two students of the Bachelor of Mathematics at the Universidad Antonio Nariño (UAN), after an intervention process carried out with two subjects such as Mathematics Didactics II and History of the math.